Original articleCD133/CD15 defines distinct cell subpopulations with differential in vitro clonogenic activity and stem cell-related gene expression profile in in vitro propagated glioblastoma multiforme-derived cell line with a PNET-like component - Kahlert, Ulf D.; Bender, Noemi O.; Maciaczyk, Donata; Bogiel, Tomasz; Bar, Eli E.; Eberhart, Charles G.; Nikkhah, Guido; Maciaczyk, Jaroslaw (Folia Neuropathologica, 2012)
Glioblastoma multiforme (GBM), as many other solid tumours, contains a subpopulation of cells termed cancer stem-like cells responsible for the initiation and propagation of tumour growth. However, a unique immunophenotype/surface antigen composition for the clear identification of brain tumour stem cells (BTSC) has not yet been found. Here we report a novel code of cell surface markers for the identification of different cell subpopulations in neurospheres derived from a GBM with a primitive neuroectodermal tumour (PNET)-like component (GBM-PNET). These subgroups differ in their CD133/CD15 expression pattern and resemble cells with different stem-like genotype and developmental pathway activation levels. Strikingly, clonogenic analysis of cultures differentially expressing the investigated markers enabled the identification of distinct subpopulations of cells endowed with stem cell characteristics. High clonogenicity could be found in CD133–/CD15– and CD133+/CD15+ but not in CD133–/CD15+ cells. Moreover, cell subpopulations with pronounced clonogenic growth were characterized by high expression of stem cell-related genes. Interestingly, these observations were unique for GBM-PNET and differed from ordinary GBM cultures derived from tumours lacking a PNET component. This work elucidates the complex molecular heterogeneity of in vitro propagated glioblastoma-derived cells and potentially contributes to the development of novel diagnostic modalities aiming at the identification of the brain tumour stem-like cell population in a subgroup of GBMs.